PENERAPAN HUKUM TERHADAP ANGGOTA PERWIRA TINGGI POLRI YANG MELAKUKAN TINDAK PIDANA PEMBUNUHAN BERENCANA YANG BERDAMPAK PADA TINGKAT KEPERCAYAAN MASYARAKAT KEPADA INSTITUSI POLRI (STUDI KASUS PERKARA FERDY SAMBO PUTUSAN MAHKAMAH AGUNG NOMOR 813 K/PID/2023) - Budi Pratama, Arya; Gultom, Potler (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
This research examines the application of the law to criminal acts of premeditated murder involving high-ranking National Police officers with a case study of the Ferdy Sambo case based on Supreme Court Decision Number 813 K/Pid/2023. The focus of the research is directed at two main aspects: first, the legal mechanisms applied in handling criminal acts of premeditated murder involving high-ranking Polri officers; second, the effectiveness of imposing sanctions in increasing public trust in the image and reputation of the National Police. The research method used is normative juridical, with an analysis-based approach to statutory regulations, court decisions, legal doctrine and related literature. This research found that legal mechanisms have been implemented according to procedures, although they face challenges in ensuring transparency and accountability. Meanwhile, imposing sanctions on Ferdy Sambo is seen as a significant step in enforcing the law, but its impact on increasing public trust still requires further strengthening through institutional reform and improving the internal monitoring system.